EFEKTIVITAS PIJAT AKUPRESUR TERHADAP MUAL MUNTAH PADA IBU HAMIL TRIMESTER I DI PUSKESMAS JAMBU HILIR - Dwiarti, Rizka; Yuliastuti, Erni; Suhrawardi, Suhrawardi; Megawati, Megawati (Seroja Husada: Jurnal Kesehatan Masyarakat, 2025)
Background: Nausea and vomiting are frequent in the first trimester due to hormonal changes. A preliminary study at Jambu Hilir Health Center showed all eight first-trimester pregnant women (100%) experienced these symptoms. Acupressure at the P6 point is a safe method believed to reduce nausea by affecting the nervous system and digestion. This study examines its effectiveness in alleviating nausea and vomiting. Objective: To determine the effectiveness of acupressure at the PC6 (Nei Guan) point in reducing NVP among first-trimester pregnant women. Methods: This quasi-experimental study used a one-group pretest-posttest design. A total of 27 pregnant women in their first trimester were selected using purposive sampling. NVP severity was measured using the PUQE (Pregnancy-Unique Quantification of Emesis and Nausea) score before and after acupressure. Data were analyzed using the Wilcoxon Signed-Rank Test. Results: Before intervention, 85.2% experienced mild and 14.8% moderate NVP. After acupressure, 100% experienced only mild symptoms. Statistical analysis showed a significant difference (p = 0.000).